Actions speak louder than words; pediatricians, gynecologists, nurses, and other mothers’ perspectives on the human papillomavirus vaccine: an Istanbul multicenter study - Parlak, Burcu; Uğurlucan, Funda Güngör; Gökçay, Emine Gülbin (Frontiers in Public Health, 2024)
Introduction Gynecologists and pediatricians have an essential duty to prevent cervical cancer. In this study, we compared the compliance of gynecologists (n = 22) and pediatricians (n = 49) with nurse/midwife (n = 66) and non-medical moms (n = 120) with regards to cervical cancer precautions. Methods A questionnaire was used to gather data on their demographics, personal vaccination and screening practices, children’s immunization status, and awareness of cervical cancer prevention. Results The findings demonstrated that gynecologists and pediatricians were better than others at understanding the risk factors and prevention of cervical cancer. It was noted that compared to other groups, physician mothers and their offspring had higher vaccination rates (n = 13, 18.3%; n = 10, 29.4%, respectively). Medical professionals typically provided thorough and accurate answers to informational questions. More frequent Pap smear tests were performed by gynecologists. It was noted that mothers who worked as pediatricians and nurses/midwives neglected their own screening needs. Discussion This questionnaire survey sought to ascertain Istanbul’s health professionals’ present opinions regarding HPV vaccination. Healthcare professionals should be the first to receive information on HPV vaccination and cervical cancer incidence reduction. The public could then readily use them as an example.